Effect of PSB and vermicompost on yield and quality of garlic (Allium sativum) (Current Horticulture, 2024)
An experiment was conducted at R B S College, Bichpuri, Agra, during winter season of 2019-21 to find out the effect of phosphorus-solubilizing bacteria and vermicompost on yield and quality of garlic. The experiment was laid out in Randomized Block Design having three replications and seven treatments. The treatments were T1 (control), T2 (50% RDF + PSB), T3 (50% RDF + vermicompost), T4 (50% RDF + vermicompost + PSB), T5 (80% RDF + PSB), T6 (80% RDF + vermicompost) and T7 (80% RDF + vermicompost + PSB). The application of 80% RDF + vermicompost + PSB) (T7) recorded significantly maximum plant height (72.4 cm), green leaves/ plant, leaf length (60.9 cm), leaf width (1.69 cm), Fresh weight of top (15.60 g), polar diameter of bulbs (5.28 cm), equatorial diameter of bulbs (4.86 cm), neck thickness of bulbs (9.47 mm), highest longest clove (3.62 cm), total bulb yield (155.5 q/ha)dry weight of bulb (19.01 g) and leaves (1.98 g). While, all parameters were recorded minimum in the control.
Keywords: Vermicompost; Growth; Yield; Quality; Bulbs; Phosphate-solubilizing bacteria